Approaching sites of action of drugs in clinical pharmacology: New analytical options and their challenges - Longuespée, Rémi; Theile, Dirk; Fresnais, Margaux; Burhenne, Jürgen; Weiß, Johanna; Haefeli, Walter E. (British journal of clinical pharmacology, 2021)
Clinical pharmacology is an important discipline for drug development aiming to define pharmacokinetics (PK), pharmacodynamics (PD) and optimum exposure to drugs, i.e. the concentration-response relationship and its modulators.